Chemical constituents profiles and antibacterial activity of psidium guajava leaves essential oil - Nor Naimah, Hussin; Noor Suhana, Adzahar; Lee, Thong Chuan; Venugopal, Jayarama Reddy (Trans Tech Publications, 2021)
The chemical constituents of Psidium guajava essential oil was analyzed by using Gas Chromatography-Mass Spectrometry. The essential oil was obtained from dried leaves by hydrodistillation method using a Clevenger apparatus. From the initial screening, 20 components were detected with different amounts traced. The most abundant constituents observed in the oil were Limonene (23.39%), Caryophyllene (18.19%), Cyclooctasiloxane (14.46%), and Pinene (13.50%). The essential oil showed significant antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Enterococcus faecalis and Bacillus cereus with inhibition range of 6-25 mm. The profile of chemical constituents present in the oil able to serve as preliminary screening of the bioactive components posses in a natural plants for investigating antibacterial properties in regenerative medicine.